Reassessment of hydrofluoric acid desilicification in the carius tube digestion technique for Re-Os isotopic determination in geological samples - Li, J.; Zhao, P.; Liu, J.; Wang, Xuan-Ce; Yang, A.; Wang, G.; Xu, J. (Wiley-Blackwell Publishing, 2015)
In this study, Re and Os isotopes were systematically determined in six geological reference materials (RMs; covering a wide range of lithologies) using the Carius tube (CT) digestion technique with and without hydrofluoric acid desilicification. Our results show that the HF desilicification increased the Re extraction efficiency (by 9–15%) evidenced from basaltic and andesitic rocks (e.g., BHVO-2, TDB-1 and AGV-2). This implies that a small proportion of Re resides in silicate phases. For mafic–ultramafic rocks (e.g., BCR-2, WGB-1 and WPR-1), Re extraction efficiencies obtained by the CT digestion with and without HF desilicification were similar. This may indicate that Re in these rocks may dominantly reside in some phases (e.g., magnetite and sulfides) that could be completely dissolved in aqua regia solutions without the aid of HF desilicification. Our results also show that the HF desilicification increased Os extraction efficiency (by 13–99%) in some RMs (e.g., BHVO-2, WGB-1 and AGV-2). This observation suggests that a portion of Os-rich trace phases may occur as inclusions in the silicate phases that act as isolators at ~ 200 mesh sizes. This study demonstrates that the HF desilicification step prior to CT digestion is important for complete extraction of Re and Os in geological samples.